Treatment of pancreatic cancer with epidermal growth factor receptor-targeted therapy - Bryan A Faller (Dove Medical Press, 2009)
Bryan A Faller, Barbara BurtnessDepartment of Medical Oncology, Fox Chase Cancer Center, Philadelphia, PA, USAAbstract: Pancreatic adenocarcinoma is a common malignancy that remains refractory to available therapies. Gemcitabine has long been the standard, first-line agent in advanced disease. The epidermal growth factor receptor (EGFR) is a commonly expressed target in pancreatic cancer that is involved in tumor proliferation, metastasis, and induction of angiogenesis. The addition of the EGFR inhibitor erlotinib to gemcitabine has recently been demonstrated to provide a small, yet statistically significant, survival benefit in advanced disease. This has prompted further research into the applications of EGFR-targeted therapy in pancreatic cancer, albeit with disappointing results. Resistance to these therapies seems highly prevalent and has been implicated in their limited efficacy. The development of rash is associated with treatment efficacy and suggests that predictive factors may one day be identified to guide appropriate patient selection for these agents. Preclinical research has shown promise that resistance to EGFR-targeted therapies can be overcome through a variety of approaches. Application of this research in clinical trials may ultimately yield an unquestioned role for EGFR-targeted therapy in the management of this disease.Keywords: cetuximab, drug resistance, epidermal growth factor receptor, erlotinib, gemcitabine, pancreatic cancer